Hidden or unnoticed? Multiple lines of evidence support the recognition of a new species of Pseudocorynopoma (Characidae: Corynopomini). Issue 1 (26th October 2020) - Malabarba, Luiz R.; Chuctaya, Junior; Hirschmann, Alice; de Oliveira, Eduardo Bitencourt; Thomaz, Andréa T.
Abstract: Species delimitation is a permanent issue in systematics. The increasing recognition of geographically isolated populations as independent lineages allowed by new methods of analysis has inflated the species‐populations dilemma, which involves deciding whether to consider separate lineages as different species or structured genetic populations. This is commonly observed between fishes of adjacent river basins, with some lineages being considered allopatric sister species and others considered isolated populations or variants of the same species. Pseudocorynopoma doriae is a characid diagnosed from its single congener by the number of anal‐fin rays and sexually dimorphic characters of males, including distinct fin colouration. The authors found variation in the colour pattern between isolated populations previously identified as P. doriae but no variation in scale or fin‐ray counts. They analysed molecular evidence at the population level and morphological differences related to life history ( e.g., colour dimorphism related to inseminating behaviour). The results provide compelling evidence for the recognition of a new species of Pseudocorynopoma despite the lack of discrete differences in meristic data. The recognition of the new species is consistent with biogeographical evidence for the long‐term isolation of the respective river drainages and with differences between the ichthyofaunal communities of these rivers.